SAT0045 The Activation of the Synovial Membrane Results in Release of Tissue Specific Biomarkers, Which in Turn can Act as Soluble Disease Activity Measures in Rheumatoid Arthritis. (9th June 2015) - Kjelgaard-Petersen, C.F.; Siebuhr, A.S.; Byrjalsen, I.; Musa, K.; Christiansen, T.; Karsdal, M.A.; Bay-Jensen, A.C.
Abstract : Background: Swollen and tender joints in rheumatoid arthritis (RA) are associated with increased turnover of the connective tissue of the joint. The synovial membrane, one of those tissues, contains type III collagen, whose breakdown and formation is highly regulated in response to changes in the inflammatory burden. Matrix metalloproteinases (MMPs) are believed to play a major role in this regulation. Previous studies have shown that type III collagen turnover, measured by serum C3M, is elevated in RA as compared to controls, and can by modulated by treatment. Objectives: 1) to confirm that C3M and MMP3 are directly released from the synovial membrane in inflammatory conditions using an ex vivo model, and 2) to investigate whether these biomarkers are associated with disease activity pain in RA patients. Methods: Human synovial membrane isolated from arthritis patients undergoing total knee replacement at Gentofte Hospital, Denmark, were cultured as explants (SME) for 3 wks with either media (w/o), 10ng/mL Tumor Necrosis Factor α (TNFα), Interleukin (IL) 1β or Transforming Growth Factor β (TGFβ)-2. Gelatin zymography and western blotting were used to detect MMP3. C3M and MMP3 were assessed in the supernatant by ELISA. Biomarker marker measures were acquired from previously established biomarker database from the LITHE study. The biomarker study included 569 patients with moderate to severe RA. The data extraction for cross-sectional analysis included age, gender, BMI, disease duration, DAS28, VAS pain, and the log-transformed biomarkers C3M and MMP3. Results: 1) Ex vivo model: Increases of 12-fold (p<0.01) and 8-fold (p<0.05) in the release of C3M were seem when the SME were treated for 10 days with the pro-inflammatory cytokines TNFα or IL1β, respectively. The increased release of C3M was in line with the release of acMMP3, with an 11-fold increase from day 7 to 21 (p<0.05) in response to TNFα and 4-5 fold increase from day 4 to 7 (p<0.01) in response to IL1β. As assessed by western blotting and gelatin zymography secretion of MMP3 was also increased by TNFα and IL1β. TGFβ2 did not increase MMP secretion of the release of C3M or acMMP3. 2) RA patients: Serum logC3M was correlated to both DAS28 (p<0.00001) and VASpain (p=0.0016) and remained highly statistical significant for both clinical outputs (p<0.001) after adjusting for age, sex, BMI and disease duration. Serum logMMP3 was also correlated to both DAS28 (p<0.00001) and VASpain (p=0.0010), which also remained highly statistical significant for both clinical outputs (p<0.00001) after adjusting for age, sex, BMI and disease duration. Conclusions: This study confirms that C3M and MMP3 are released directly from the synovial tissue and thus may serve as biomarkers of synovial turnover. Furthermore there was a strong association between DAS28, VASpain, and the biomarkers, which may indicate that these are soluble markers of disease activity. Disclosure of Interest: C. Kjelgaard-Petersen: None declared, A. Siebuhr Grant/research support from: EC FP7 programs, Employee of: Nordic Bioscience, I. Byrjalsen Employee of: Nordic Bioscience, K. Musa: None declared, T. Christiansen: None declared, M. Karsdal Shareholder of: Nordic Bioscience, Grant/research support from: EC FP7 programs, Employee of: Nordic Bioscience, A. Bay-Jensen Shareholder of: Nordic Bioscience, Grant/research support from: EC FP7 programs, Employee of: Nordic Bioscience